RED BLOOD CELL DISTRIBUTION IS INDEPENDENTLY ASSOCIATED WITH DAILY DIASTOLIC BP VARIABILITY. (April 2021) - Torbas, Olena; Kushnir, Svitlana; Rekovets, Oksana; Sirenko, Yuriy
Abstract : Objective: Previously it was shown that in a large cohort of unselected outpatients there was a strong independent association between elevated red blood cell distribution width (RDW) and increased incidence of cardiovascular events which may be associated with inflammation. The aim of our analysis was to evaluate whether RDW was independently associated with any of proven cardiovascular diagnostic markers. Design and method: We included 171 patients with arterial hypertension who had underwent all diagnostic procedures: office BP measurement, ambulatory BP monitoring (ABPM), carotid-femoral pulse wave velocity (cfPWV), cardio-ankle vascular index (CAVI), haematology test with RDW, vascular ultrasound and echocardiography. The results of Spearman correlation was after that tested in a multivariant regression model. Results: Results. Mean age of our patients was 52, 9 ± 1, 1 y/o, mean BP was 154, 4 ± 2, 4/93, 3 ± 1, 3 mmHg, mean hear rate (HR) 78, 3 ± 1, 3 bits per min, 37% men and 63% women, mean RDW was 14, 8 ± 0, 7%. Among all the parameters we have obtained, RDW was significantly inversely associated only with office systolic and diastolic BP (r = -0, 189, p = 0, 023 and r = -0, 206, p = 0, 013 respectively), daily diastolic BP (DBP) variability (r = -0, 270, p = 0, 02) and daily HR variability (r = -0, 314, p = 0, 027). Moreover, the association RDW with DBP variability remained significant even after the adjustment for office DBP, hemoglobin and erythrocytes level (beta = -0, 587, p = 0, 022), but correlation of RDW with HR variability after the adjustment for office HR and hemoglobin was not significant (beta = -0, 437, p = 0, 116) which underlines that HR variability is more associated with blood hemoglobin level. Also we did not find any significant correlations of RDW with any of arterial stiffness, vessel wall thickness, echocardiographic left ventricle mass index and other parameters. Conclusions: A significant correlation of RDW with office systolic and diastolic BP, but more an independent correlation of RDW with DBP variability may demonstrate is role as a potential interesting biomarker which may be used in future studies.